16=-2x-1

Simple and best practice solution for 16=-2x-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 16=-2x-1 equation:


Simplifying
16 = -2x + -1

Reorder the terms:
16 = -1 + -2x

Solving
16 = -1 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
16 + 2x = -1 + -2x + 2x

Combine like terms: -2x + 2x = 0
16 + 2x = -1 + 0
16 + 2x = -1

Add '-16' to each side of the equation.
16 + -16 + 2x = -1 + -16

Combine like terms: 16 + -16 = 0
0 + 2x = -1 + -16
2x = -1 + -16

Combine like terms: -1 + -16 = -17
2x = -17

Divide each side by '2'.
x = -8.5

Simplifying
x = -8.5

 

See similar equations:

| -15=22x+7 | | 7x-1=23-3x | | x+4(x-5)=2(x-5)-13 | | 4x=50 | | -3k+5(6-k)=4(-2k) | | 4(1-x)+3x=-2(x+1) | | 4X+5Y=120 | | 23=-4m+2+M | | 6(x-6)+3x=36 | | -3k+5(6-k)=4(1-2k) | | 8.9+1.2(3a-1)=14.9 | | 12x+4=8x+5 | | 12x-5x=-49 | | 1k=8k+28 | | 2x+2= | | 3x+4=10-3x-6 | | 7x+3(8-2x)=11 | | 16t-6=8t+23 | | 12x-2(x+3)=14 | | -7a-10=20-39 | | 14-3g=32 | | m-14=4 | | 5=s+10 | | 1z+81=9z-7 | | x(x+9)=52 | | m-8=-2 | | x+0.8=7.8 | | 7X+4=4(X-4)+2 | | 10m+8=7m+17 | | 5(b-5)-4b=-13 | | 4y-8y=-20 | | 8-x=12 | | 6-4y=18 | | 3(x-6)=33 | | 5+4+x=11 | | 5x=84 | | 5v+10=95 | | 5v+5+3v= | | -6z-5=7 | | 5(2+3b)=15-(b-7) | | 2h+3+4+h= | | 7a+3a= | | 2(3+6x)-5=73 | | 5p-16=-19+4p | | 6r-14=4+4r | | 13x+17x=180 | | 3n-45+2n+15=180 | | (3n-45)+(2n+15)=180 | | 10x-23=97 | | 8x+8=5x+17 | | 10x-33=5x+2 | | 3x+35=11x-45 | | 2x-3=10x-51 | | 8+11x=68+x | | 4x+11=65-2x | | 10=2-6b+14 | | 5f=20 | | 20x+3y=1 | | 4.6*q=44.16 | | 10*t=8.6443 | | 10*x=8.6443 | | 3t-4=7+2(t+3) | | 5x+20=10x | | 10x-10=8x | | 7x=42 |